2022
DOI: 10.3390/chemosensors10040129
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Study of Phytosynthesized Ag Nanoparticles and Their Activity as SERS Substrate

Abstract: The affordable and scalable synthesis of noble metal nanoparticles that are biocompatible without additional functionalization steps has been a growing field of research, stimulated by numerous prospective applications of these NPs. In the case of phytosynthesized or biogenic noble metal NPs, the mechanism of NP stabilization by biomolecules contained in each particular plant extract or living organism determines the possible applications of these NPs. In this work, we investigated Ag NPs synthesized in water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 51 publications
3
6
0
Order By: Relevance
“…The reduction of silver ions that leads to Ag NP formation on the surface of the ZnO flower-like NPs was attempted in the present work with different extracts, including G. lucidum mycoextract, but here we present only the results obtained with the chili pepper ( Capsicum annuum ) fruit extract. The latter has been recently demonstrated to mediate the formation of free-standing colloidal Ag NPs, 11,23 and that synthesis is shown here to be compatible with the G. lucidum mycoextract-mediated synthesis of ZnO NPs, producing ZnO/Ag heteroparticles. Fig.…”
Section: Resultssupporting
confidence: 55%
See 3 more Smart Citations
“…The reduction of silver ions that leads to Ag NP formation on the surface of the ZnO flower-like NPs was attempted in the present work with different extracts, including G. lucidum mycoextract, but here we present only the results obtained with the chili pepper ( Capsicum annuum ) fruit extract. The latter has been recently demonstrated to mediate the formation of free-standing colloidal Ag NPs, 11,23 and that synthesis is shown here to be compatible with the G. lucidum mycoextract-mediated synthesis of ZnO NPs, producing ZnO/Ag heteroparticles. Fig.…”
Section: Resultssupporting
confidence: 55%
“…ZnO, including ZnO nanoparticles and microstructures, has attracted the steady interest of researchers for decades. [1][2][3] The variety of its applications explains the need for different approaches to its synthesis [3][4][5][6][7][8][9][10][11] and the formation of its heterostructures with semiconductor or metal nanostructures. [4][5][6] Green chemistry approaches to nanoparticle (NP) production have the advantages of eco-friendly and hazard-free manufacturing, and economic and time-effective biosynthesis.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been indicated that the spherical structure of AgNPs is a reason for creating unremarkable Raman peaks 20 . SERS spectroscopy has been rarely reported for biosynthesized AgNPs 19,45 . Indeed, the SERS experiments represented that the feature of (phyto)-functionalization of AgNPs permits other molecules to approach the NPs surface (a distance of a few nm) to "feel" the plasmon eld of the NPs and this information is very important for other applications of the biosynthesized NPs 45 .…”
Section: Ftir and Raman Spectroscopy Analysismentioning
confidence: 99%